2021
DOI: 10.1590/1413-81232021262.40812020
|View full text |Cite
|
Sign up to set email alerts
|

Necessidades em Saúde dos adolescentes na perspectiva dos profissionais da Atenção Primária à Saúde

Abstract: Resumo O reconhecimento das necessidades em saúde é essencial na elaboração de ações e políticas públicas. Objetivo: analisar o reconhecimento e a satisfação das necessidades em saúde dos adolescentes, a partir da perspectiva de profissionais da Atenção Primária à Saúde. Método: estudo qualitativo, exploratório e descritivo, analisou 15 entrevistas realizadas com profissionais da Atenção Primária à Saúde que atuam no Distrito Sanitário III em Recife, Pernambuco, Brasil, há um ano ou mais. Foi realizada análise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
0
2
0
13
Order By: Relevance
“…28,35 Thus, the understanding of a given phenomenon, such as the contradiction established between the need to provide comprehensive health care to adolescents in the SUS and the reality that presents robust rates of HCSPC in this population group, becomes possible through the construction of a criticalreflexive professional consciousness, which considers the determination of the health process of individuals or social groups through the perception of their gender, social class, and ethnic relations, in addition to exploring the processes arising from the economic, legal, and ideological model of a given society in a given historical moment. 15…”
Section: Comprehensiveness In Adolescent Hospitalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…28,35 Thus, the understanding of a given phenomenon, such as the contradiction established between the need to provide comprehensive health care to adolescents in the SUS and the reality that presents robust rates of HCSPC in this population group, becomes possible through the construction of a criticalreflexive professional consciousness, which considers the determination of the health process of individuals or social groups through the perception of their gender, social class, and ethnic relations, in addition to exploring the processes arising from the economic, legal, and ideological model of a given society in a given historical moment. 15…”
Section: Comprehensiveness In Adolescent Hospitalizationsmentioning
confidence: 99%
“…13 Concerning the identification of the health needs of adolescents, one study identified the invisibility of this population segment for actions that meet their needs in the context of PHC, 14 such as demands related to family planning, sexually transmitted infections, and family conflicts. 15 In this context, it is noteworthy that actions in PHC are essential for improving the quality of life and health of the population; hence, knowing the trends of hospitalization can guide the investment of public policies in PHC. 11 This study is justified because it is understood that, in the implementation of the Brazilian Public Health Policy, there is a shortage of health promotion and disease prevention actions aimed at adolescents in PHC, which can ultimately culminate in developing signs and symptoms that evolve into a HCSPC.…”
Section: Introductionmentioning
confidence: 99%
“…As necessidades em saúde são, também, necessidades de reprodução social. Abrangem diferentes dimensões da vida e não se restringem a problemas de saúde ou doenças que acometem os indivíduos, podem ser de âmbito físico, psíquico, afetivo, social, cultural ou político, de modo que a qualidade de vida e saúde são dependentes da sua satisfação (Barros et al, 2021).…”
Section: Métodounclassified
“…respostas às demandas dessa população, com base em relações horizontais e territorializadas entre os diferentes contextos e cenários de cuidado (BRASIL, 2017;BARROS et al, 2021).…”
Section: Recima21 -Revista Científica Multidisciplinar Issn 2675-6218unclassified